Tribute to Georges Villain (1881-1938), Professor at the Dental School of Paris, During the Great War - Xavier Riaud (Journal of Dental Problems and Solutions - Peertechz Publications, 2015)
Georges was born in Paris on May 31, 1881. Coming from a modest family and losing his father at an early age, he became the mechanic apprentice of a Parisian dentist called Georges Viau. As soon as he finished his apprenticeship, he went abroad to study dentistry in England with a dentist who soon became his private tutor. During his stay, he acquired a good knowledge of English. In 1902, when he returned to Paris, he attended the Dental School in Paris. In 1902, he became an assistant in the class of orthodontics of the Dental School of Paris and then a demonstrator in 1904. In 1903, he was qualified dental surgeon from the Faculty of Medicine in Paris. In 1905, Charles Godon, founder and head of the Dental School of Paris since 1880, had a premonition about the excellence of the young man and encouraged him to undertake a trip in the United States to study in that school. Upon his arrival, he enlisted at the University of Pennsylvania. He received his Doctor of Dental Surgery degree in 1906 [22].